Can Smart Phones Support the Homeless during the COVID-19 Pandemic: A Case Study in Malaysia - Jasni, Mohd Alif; Abu Bakar Ah, Siti Hajar; Omar, Noralina; Che Mohd Nasir, Norruzeyati (Malaysian Communications and Multimedia Commission (MCMC), 2021)
Smartphones are a necessity for society today and was especially important in helping the homeless throughout the COVID-19 pandemic. The diversity of functions available within a smartphone was able to provide significant benefits for homeless people in the face of the pandemic. A qualitative study was conducted by interviewing seven homeless persons to identify the perspectives of those who are homeless regarding the benefits of smartphones. Based on these perspectives, five themes about the benefits of smartphones were obtained. The findings indicate that smartphones enable people to stay in touch and communicate with family and friends, the acquisition of information on assistance provided by the government, the acquisition of information on financial aid, food distribution, and necessities provided by NGOs, the acquisition of information on COVID-19 prevention measures and to get news related to the latest COVID-19 situation. This study proved that smartphones were beneficial to homeless people in the face of the pandemic. The difficult situation during the pandemic made mobile phones a necessity to enable homeless people to cope with life on the streets.